Republic of Ghana Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
This 2014 Report on the Observance of Standards and Codes in Accounting and Auditing (ROSC A&A) is the second review for Ghana. Its main objectives are to: assess the degree to which the policy recommendations of the 2004 review have been implemented, identify any emerging issues since the last review and develop policy recommendations that, once implemented, would further enhance the quality of financial reporting in the country. While growth has been spurred by favorable commodity prices for gold and cocoa, the start of commercial production of oil and a booming services sector, there is still room for improvement in the business environment, business confidence and financing of the economy. The implementation of the policy recommendations contained in this report will contribute to improved business environment and investor confidence, an essential factor for economic growth.